DAMPAK PELAYANAN SAMSAT KELILING TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA SURAKARTA - Selva Dwi Cahya (PROSEDING, 2022)
The purpose of this study was to examine the effect of mobile Samsat services on the Compliance of Motor Vehicle Taxpayers in the City Surakarta. In this study, surveyed 494,370 Motor Vehicle Taxpayers registered at the Surakarta Samsat office. The Slovin formula was used to select a sample of 100 participants for the sampling procedure. Reliability and validity tests, normality tests (eg T and F tests), heteroscedasticity tests (eg autocorrelation tests), and determination tests are all included in the multiple linear regression analysis (R2). Based on hypothesis testing, taxes and access to facilities have a major effect on compliance with motorized vehicle taxpayers, while the complaint center and website have no significant effect on compliance. Motor vehicle taxpayers are more likely to comply with tax laws when they have access to facilities such as complaint centers and websites. web, according to the findings of the F test. The result of the R2 test, on the other hand, shows the number 0.679. There is an independent variable effect of 67.9% on the dependent variable, and the effect of an additional component of 32.1%. Keywords : Tax Access, Facilities, Complaint Center, Website ,Taxpayer Compliance.